"Cyberising" God: A Theo-Phenomenological Investigation of Religion Online and Online Religion - Rahman, Fazlul (DINIKA : Academic Journal of Islamic Studies, 2016)
A strong demand to rejuvenate the package of religion becomes inevitable consequence of current globalization era which is marked by the emerging of the giant network of networks, the Internet. By its high user and penetration number, the Internet creates some significant appropriations in the current society’s social and religious lives. Religion Online and Online Religion are of many products of religion’s appropriation effort to the coming of Internet. Using theo-phenomenological approach to analyze an example of Religion Online and Online Religion, this paper concludes that Internet not only is a powerful technology that could change the face of religion but it also functions as a religion itself, that helps people feel God’s presence.Keywords:globalization, internet, religion online and online religion